2016
DOI: 10.1111/idj.12213
|View full text |Cite
|
Sign up to set email alerts
|

Self-report of gingival problems and periodontitis in indigenous and non-indigenous populations in Chiapas, Mexico

Abstract: Indigenous people living in rural areas are more likely to have periodontitis. It is necessary to promote oral health practices in indigenous and marginalised populations with a focus on community-oriented primary care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 27 publications
0
10
0
2
Order By: Relevance
“…The validity of selfreported symptoms is comparable to clinical examinations for assessing periodontal health 26 . Furthermore, when large-scale data, representative of community residents, are collected, self-reported questionnaires are economical and convenient; in addition, the subjective individual symptoms are more relevant to the use of dental services compared with the diagnoses of periodontal health by a dental clinician 20,27,28 . Accordingly, use of a self-reported questionnaire is a valid method of analysis for this present study.…”
Section: Methodsmentioning
confidence: 99%
“…The validity of selfreported symptoms is comparable to clinical examinations for assessing periodontal health 26 . Furthermore, when large-scale data, representative of community residents, are collected, self-reported questionnaires are economical and convenient; in addition, the subjective individual symptoms are more relevant to the use of dental services compared with the diagnoses of periodontal health by a dental clinician 20,27,28 . Accordingly, use of a self-reported questionnaire is a valid method of analysis for this present study.…”
Section: Methodsmentioning
confidence: 99%
“…A recent update from the American Academy of Periodontology indicated that the classification of periodontal disease should include evaluation of the following: (i) gingival attachment level; (ii) chronic versus aggressive periodontitis; and (iii) localised versus generalised periodontitis, with a focus on the percentage of affected teeth. The second method is a subjective measurement that identifies periodontal disease through self‐reported measures. In the objective measurement, severe periodontitis is defined as having one or more site(s) with a probing pocket depth ≥ 6 mm or clinical attachment loss (CAL) ≥ 5 mm.…”
Section: Introductionmentioning
confidence: 99%
“…Self-reporting health conditions is often used in epidemiologic surveillance for general and dental health [51,52,53,54]. Such approach in dental situations has been applied to periodontal disease [51,55,56], caries [57,58], tooth loss [59,60], or presence of teeth [61,62]. Future studies would allow measuring more accurately the financial burden of dental care in Mexican households.…”
Section: Discussionmentioning
confidence: 99%